SPBE Integration Strategy Through Enterprise Architectur - Winarko, Heru; Sartika, Ika (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The digital transformation of the public sector in Indonesia has fostered the need for integrated public services through the implementation of the Electronic-Based Government System (SPBE). However, low interoperability among information systems remains a major challenge that hampers service efficiency. This article conducts a literature review of 50 national journals related to SPBE integration based on Enterprise Architecture. The findings highlight the crucial role of Enterprise Architecture in aligning business processes, data, and technology across institutions, thereby enhancing public service interoperability. This study also offers strategic recommendations such as adopting the TOGAF framework, strengthening data infrastructure, and formulating integrative policies as actionable solutions to support unified and sustainable digital government governance.